2008
DOI: 10.1111/j.1365-2966.2008.13405.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical polarimetric study of open clusters: distribution of interstellar matter towards NGC 654

Abstract: We present new B, V and R linear polarimetric observations for 61 stars towards the region of the young open cluster NGC 654. In this study we found evidence for the presence of at least two layers of dust along the line of sight to the cluster. The distances to the two dust layers are estimated to be ∼ 200 pc and ∼ 1 kpc which are located much closer to the Sun than the cluster (∼ 2.4 kpc). Both the dust layers have their local magnetic field orientation nearly parallel to the direction of the Galactic plane.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…The instrumental polarization of AIMPOL on the 1.04-m ST has been monitored since 2004 for different projects and is 0.1% in different bands (e.g., Rautela et al 2004;Medhi et al 2007Medhi et al , 2008Medhi et al , 2010Eswaraiah et al 2011Eswaraiah et al , 2012. No correction for the instrumental polarization was applied to the data obtained with IFOSC since the instrumental polarization of the instrument on the 2-m telescope is <0.05 per cent.…”
Section: Polarimetrymentioning
confidence: 99%
“…The instrumental polarization of AIMPOL on the 1.04-m ST has been monitored since 2004 for different projects and is 0.1% in different bands (e.g., Rautela et al 2004;Medhi et al 2007Medhi et al , 2008Medhi et al , 2010Eswaraiah et al 2011Eswaraiah et al , 2012. No correction for the instrumental polarization was applied to the data obtained with IFOSC since the instrumental polarization of the instrument on the 2-m telescope is <0.05 per cent.…”
Section: Polarimetrymentioning
confidence: 99%
“…In fact, the instrumental polarization of ST has been monitored since 2004 within other projects as well (e.g. Medhi et al, 2007;Medhi et al, 2008;Pandey et al, 2009). These measurements demonstrated that it is invariable in all B, V and R pass bands.…”
Section: Optical Polarimetrymentioning
confidence: 98%
“…The focal plane instrument used was the ARIES Imaging Polarimeter (AIMPOL) (Medhi et al (2008), Pandey et al (2009)) which consists of a Wollaston prism used to split the incident unpolarized beam into two orthogonally polarized ordinary and extraordinary components and a rotatable half-wave plate (HWP) used to alter the polarization state of the light wave. The observations of Comet C/2012 L2 (LINEAR)…”
Section: Observation and Data Reductionmentioning
confidence: 99%
“…The gain and the read-out noise of the CCD are 11.98 e − /ADU and 7.0 e − , respectively. Four sets of exposures of each 60 s were made on both the nights of observation.The detailed description of the instrument is given in Rautela et al (2004) and Medhi et al (2008Medhi et al ( , 2010.…”
Section: Observation and Data Reductionmentioning
confidence: 99%